Scaffolding Arabic Syntax Learning: An Examination of Introductory Nahwu Materials for Novice Students - Muhamad Solehudin; Aufa Hanin Salsabil; Sultan Abdus Syakur (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
This study investigates the pedagogical structure and scaffolding mechanisms within Pengantar Belajar Ilmu Nahwu by Al-Habib Hasan bin Ahmad Baharun, a foundational Arabic syntax textbook widely used in pesantren education in Indonesia. While previous studies on Arabic grammar learning have primarily emphasized external scaffolding through instructional strategies or digital technologies, limited attention has been paid to the internal scaffolding embedded within traditional nahwu textbooks themselves. Grounded in Vygotsky’s Sociocultural Theory and the scaffolding framework of Wood, Bruner, and Ross, this qualitative content analysis examines how the text sequentially supports novice learners in mastering Arabic syntax. The findings identify three interrelated scaffolding stages conceptual, procedural, and integrative through which syntactic awareness is progressively developed using simplified examples, repetitive sentence patterns, and contextualized explanations. A distinctive pedagogical feature of the book is its early emphasis on phonological recognition (ḍammah, fatḥah, and kasrah) prior to introducing abstract grammatical terminology, which functions as a cognitive bridge for beginners. The study concludes that Pengantar Belajar Ilmu Nahwu exemplifies an effective model of internal scaffolding, demonstrating how traditional Arabic grammar materials can align with contemporary educational psychology to support novice syntax learning in pesantren and similar educational contexts.